PENINGKATAN KESADARAN MASYARAKAT UNTUK PENGELOLA SAMPAH MANDIRI MELALUI IMPLEMENTASI TEKNOLOGI TEPAT GUNA - Eny Boedi Orbawati; Retno Rusdjijati; Yun Arifatul Fatimah; Oesman Raliby; Didin Saepudin; Awaluddin Setya Aji; Doddy Ardjono; Andreas Pandiangan; Arizal Arizal; Agus Setyowidodo (Jendela Inovasi Daerah, 2021)
Currently the condition of Magelang Muncipality is said to be a "waste emergency" considering the rate of waste production (waste volume) which continues to increase every year is inversely proportional to the rate of waste reduction programs and the decreasing capacity of TPSA. At the upstream level, various waste reduction program efforts have been carried out by the Magelang Municipality Government, including the Waste Bank program, Organic Village, Reduce, Reuse and Recycle Waste Disposal Sites (TPS3R), and Integrated Waste Processing Sites (TPST) which have been carried out since 2012 was only able to reduce waste generation by 9.3% of the total waste generated. The main problem of waste management in Magelang Municipality lies in limited land. Therefore, it is necessary to study the efforts that will be developed as far as possible that do not require a large area of ​​land but can produce optimal waste management. In addition, these efforts involve various parties, especially those that focus on community empowerment. This research uses desk research method. The results of the study explain that waste management is not only the duty and responsibility of the Regional Government but also the duty and responsibility of the community. The role of various parties, including local governments, stakeholders, and most importantly the community, is the largest producer of waste. Hereinafter known as community-based waste management or Community Based Solid Waste Management (CBSMW). CBSMW is a waste management system that is planned, compiled, operated, managed, and owned by the community. The goal is to create community independence in maintaining environmental cleanliness through environmentally friendly waste management. The principles of CBSMW are community participation, independence, efficiency, environmental protection, and integration.